Energy, exergy and exergoeconomic analysis of solar-assisted vertical ground source heat pump system for heating season - Unal, Fatih; Temir, Galip; Koten, Hasan (KOREAN SOC MECHANICAL ENGINEERS, 2018)
The purpose of this study is to evaluate the experimental performance of a solar assisted vertical ground source heat pump system (VGSHP) for the winter climatic conditions of Mardin, which is in the South-Eastern Anatolia region of Turkey. For this aim, an experimental analysis was performed on solar assisted VGSHP system, which was designed to meet the heating needs of an experimental room, during the heating season (10.01.2013/03.31.2014). The experimentally obtained results were used to calculate energy, exergy and exergoeconomic analyses of the system and its components. The energy efficiency, exergy efficiency and exergoeconomic factors of the entire system were 67.36 %, 27.40 % and 60.51 %, respectively. In this study, the system was proposed for disseminating the use of alternative technologies supported by renewable energy systems and it has been tested for the first time in Mardin to meet its heating needs with convectional systems. The experimental results showed that the proposed solar assisted VGSHP system can be used for residential heating in Mardin and similar regions. As a result, it has been detected that the system is very effective in both reducing energy consumption and decreasing emissions of green-house gases.
Keywords: Energy; Exergy; Exergoeconomic; Heat pump; Ground source heat pump; Solar assisted ground source heat pump; Thermodynamic analysis; Engineering